Finite Element Analysis to Study Tensile Strength Differences between Free and Attached Ear Lobules. Issue 1 (17th January 2023) - Vathulya, Madhubari; Sarkar, Subrato; Verma, Vaishali; Singh, Indra Vir; Kandwal, Pankaj
Abstract : Summary: Recurrent ear lobule deformity is a chronic condition with aesthetic implications. The problem is normally addressed by certain improvisations of the traditional lobuloplasty technique. These include introduction of autologous tissue components like cartilage pieces to improve the structural integrity. Certain authors also advocate a different site for repiercing of the ear hole away from the lobuloplasty scar. Our study tries to understand the differences in the tensile strength between free and attached ear lobules, using finite element analysis. Eighteen healthy female volunteers with attached (eight subjects) and free ear lobules (10 subjects) were chosen, and the lobules were scanned using Artec 3D scanner. The model was then converted to free form or attached form (opposite to the form in which it was present originally) by decreasing or increasing the area of contact using geomagic software. Finite element analysis was then performed on both the models, and their yield max and, hence, the maximum load at the yield max at 0.7 strains according to previous studies were estimated and compared. The yield max and the corresponding load were found to be lesser in the free variety than in the attached variety. This experiment helps us to understand that when a structural difference in the ear lobule surgically may bring about a change in the tensile strength of the lobules. However, further clinical trials are required to clinically translate the same.